NATURAL HISTORY OF RHEUMATIC HEART DISEASE, A 12 YEARS OBSERVATIONAL STUDY PENICILLIN BITES THE MUSCLE BUT HEALS THE HEART - Rizvi, Syed Faiz-ul-Hassan; Kundi, Asad ullah; Naveed, Atif; Faiz, Abdullah; Samad, Abdus (Journal of Ayub Medical College Abbottabad, 2014)
Background: Rheumatic Heart Disease (RHD) is a major cause of cardiovascular morbidity and mortality in young individuals, in developing countries. Long term studies regarding natural history of RHD in Pakistan have not been reported in literature. We present our follow up observations on RHD patients at the end of 12 years since our first survey conducted in rural communities in 1994. Methods: Our study patients were known cases of RHD, diagnosed in cross sectional survey of rural areas of Rahimyar Khan in 1994. Second survey conducted in 2006, in which these RHD patients were evaluated in detail with history/Physical examination, 12 lead ECG, X-ray chest PA view and Echo/Doppler studies at Sheikh Zayed Medical College Rahimyar Khan. Results: Out of 57 patients enrolled in 1994, 21 patients (37%) were available for further evaluation. Overall mortality was 23%. Male to female ratio was 1:1.62. Age ranges between 20-80 years with mean of 43 years. Only 6 patients (29%) were taking rheumatic prophylaxis (RP) and six patients had recurrent RF. Five patients (24%) developed new aortic regurgitation (AR) and 38% increased in grade of severity of lesions on Echo (none of them was on RP). Regression of mild lesions noted in six patients (all of them were on RP). Two patients underwent surgery. 10% developed new atrial fibrillation. Conclusion: Unabated RF/RHD led to a very high mortality. Favourable out come observed with prophylaxis even for short period on mild or moderate RHD. Patients not on RP had severe diseases. This small study is a big blow to our claims of combating RF/RHD in the 21st century. Keywords: Heart, rheumatic, natural history, penicillin